Characterising the progress in HIV/AIDS research in the Middle East and North Africa. (17th April 2013) - Saba, Hanan F; Kouyoumjian, Silva P; Mumtaz, Ghina R; Abu-Raddad, Laith J
Abstract : Objectives: The Middle East and North Africa (MENA) region is perceived to have limited HIV data. The objective of this study was to quantitatively characterise the progress in HIV research in this region since the discovery of the epidemic. Methods: Four indices were defined and implemented to measure the progress of HIV research using the PubMed, Embase, MENA HIV/AIDS Epidemiology Synthesis Project and US Census Bureau HIV/AIDS Surveillance databases. The four indices provide complementary measures to characterise different aspects of the progress of HIV research. Results: A total of 2118, 2352, 683 and 4889 records were identified through the PubMed, the Embase, the Synthesis Project and the HIV Prevalence indices, respectively. The proportion of the total global HIV records that relate to MENA is 1.2%. Overall, the indices show steady progress in the number of new records every year, with an accelerated pace in the last few years. The rate of progress in MENA was also higher than the rate of progress in HIV records globally. There is no evidence so far of stabilisation or a peak in the number of new records year by year. About half of the records were produced after the year 2005. The number of records shows large heterogeneity across countries. Conclusions: MENA has witnessed a rapid growth in HIV research over the last decade. However, there are still large gaps in HIV scientific evidence in the region, and the progress is far from being uniform across countries. Ongoing and future research needs to be geared towards academic standard and production of scientific publications.